PROFIL PENDAKI GUNUNG PADA KOMUNITAS PGI KORWIL RIAU DI KOTA PEKANBARU - Imran, Muhammad; Bahri, Syamsul (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Research on the development of urban communities to do because that is marked by the advance of science and technology as well as the development of industrialization, this becomes a motor of economic development, it raises issues environmental concern such as pollution, environmental degradation and destruction of natural resources that cannot be renewed. Environmental issues is one who becomes the driving factor in the birth and development of the social groups in the form of such a community, PGI (Mountaineers Indonesia) with the purpose to provide education, science and activity the wild and besides that there are also environmental preservation activities in the mountains and forests. And interest on the curiosity of anyone and from what social class, as a social group, how can the community build the identity of the Group and develop the symbols of life and different styles or with a group or community other social as well as what activities or programs in the areas of social, economic, and cultural community do PGI Korwil Riau in strengthening a sense of social solidarity among members of the community as well as society. The development of qualitative research methodology within the next twenty years it's quite rapidly, so that a variety of methods and approaches as well as experimental data analysis strategy is already done in many studies, including data analysis methods also participated developing. As explained in the previous section that in the tradition of qualitative research are some of the methods of data collection also is a method of data analysis so that method against the explanation at the same time discuss the methods, functions both as a methods of data collection and data analysis. from this research it is known that members of the community come from among the students and workers, developing and establishing the identity of the group through social media, events, and activities of the environment. It also has a Community program in the field of environment, social and economic. Keywords: community, environment, social class, Social Identity, social solidarity.